Influence of chronic dietary carbohydrate supplementation on plasma cytokine responses to exercise - Cox, A. J.; Pyne, D. B.; Cox, G. R.; Callister, R.; Gleeson, M. (International Journal of Sports Medicine, 2010)
This study examined the influence of 28 days of dietary carbohydrate (CHO) supplementation on plasma cytokine responses to cycle ergometry. Sixteen highly trained male cyclists and triathletes (age: 30.6±5.6 y; VO2max: 64.8±4.7 mL.kg-1.min-1; mean±SD) participated in the study. One group (n=8) consumed a higher-CHO (8.5±1.7 g.kg-1 body mass.day-1) diet for 28 days; a second group (n=8) consumed a moderate-CHO diet (5.3±0.4 g.kg-1.day-1). Total daily energy intakes were similar between the two groups. Cytokine responses to cycle ergometry were assessed prior to and again following the dietary intervention period. The cycle ergometry protocol involved 100 min steady state cycling at 70% VO2max followed by a time trial of ~30 min. Athletes were provided with 15 mL.kg-1.h-1 of water during each trial. Blood samples were collected pre-, immediately post- and 1 h post-exercise for determination of plasma glucose and pro-inflammatory (IL-6, IL-8) and anti-inflammatory (IL-10, IL-1ra) cytokine concentrations. Cytokine responses to cycle ergometry were not substantially altered following the 28-day higher-CHO diet. In contrast, following the 28-day moderate-CHO diet, there were ~30-50% reductions (p=0.08-0.11) in anti-inflammatory cytokine responses post-exercise. These findings suggest that increased dietary CHO content alone does not effectively attenuate the pro-inflammatory cytokine response to exercise, however, there may be a small reduction in the anti-inflammatory cytokine response.